Cash waqf crowdfunding model as a source of business capital for Kelompok Usaha Warung Sejahtera - Nurul Huda; Muhammad Rofi'i; Ariel Nian Gani; Dwina Reflie Dimitra; Maheswara Prastiwi; Taufik Nur Hidayah; Webryana Mendy Feehily (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, contributing significantly to the Gross Domestic Product (GDP) and providing 96.87 percent of the employment opportunities. Despite their continued growth, particularly in Tanjung Priok, MSMEs face challenges, especially in accessing capital. The Warung Sejahtera Business Group in Tanjung Priok exemplifies micro-enterprises struggling with capital limitations, market access, and a lack of digital and managerial knowledge. The community service activities focus on improving access to capital through crowdfunding waqf in collaboration with SatuWakaf Indonesia, leveraging untapped cash waqf potential to strengthen MSME production capital and stimulate local economic growth. The method used is Participatory Action Research (PAR), involving 34 participants. Pretest and post-test analyses showed a 53.17 percent average increase in understanding of waqf and SatuWakaf as alternative funding sources. The community service team has initiated cooperation with SatuWakaf Indonesia, providing initial guidance to partners on accessing waqf- based capital and creating opportunities for further collaboration. In addition, this community service activity contributed to the establishment of a cash waqf nazir institution, this institution can be a place for cash waqf crowdfunding to help meet the capital needs of MSMEs.